2011
DOI: 10.1308/147870811x13137608454939
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon-operated ultrasonography in a one-stop shoulder clinic

Abstract: Ultrasonography has become an essential adjunct to clinical examination when assessing patients with suspected rotator cuff pathology. [1][2][3][4][5][6] The advantages of portable shoulder ultrasonography are that the surgeon can evaluate the integrity of the rotator cuff immediately in a one-stop clinic. This allows an efficient and effective treatment plan to be initiated. Shoulder ultrasonography is non-invasive, has virtually no side effects and allows the rotator cuff to be visualised dynamically during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Seagger et al [31] described a one-stop strategy for managing shoulder pain, in which patients were evaluated by a surgeon, underwent diagnostic ultrasonography, and received a therapeutic injection if appropriate during the same clinic visit. Ultrasonography was performed by the surgeon using a portable machine.…”
Section: Discussionmentioning
confidence: 99%
“…Seagger et al [31] described a one-stop strategy for managing shoulder pain, in which patients were evaluated by a surgeon, underwent diagnostic ultrasonography, and received a therapeutic injection if appropriate during the same clinic visit. Ultrasonography was performed by the surgeon using a portable machine.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have demonstrated that ultrasound‐guided knee injections can save money over palpation‐guided injections by prolonging time to reinjection (150). Others demonstrated cost savings of MSUS over MRI through reduced utilization, reduced time to diagnosis (22), and reduced number of visits to treat the condition (23, 231). Nevertheless, cost consideration is necessary to guide use and mitigate societal risks through overutilization and consumption of health care resources.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been reports of ultrasound scans being performed immediately in the shoulder clinic, obviating the need for a separate scan appointment [6][7][8][9]. These 'one stop' scans have been performed by both sonographers and appropriately trained surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…In our unit, 'one stop' or 'office-based' scanning is not yet widely available [6][7][8][9]. Patients are usually filtered through to the shoulder clinic by a musculoskeletal assessment team (MATS) who take all referrals from the local general practitioners.…”
Section: Introductionmentioning
confidence: 99%